Early childhood development practices in a remote Aboriginal Community Controlled Health Services setting. (8th July 2022) - Bromley, Jane; Sherrard, Stephanie; Atkinson, David; Marley, Julia V.; Henderson‐Yates, Lynette; Griffiths, Emma
Abstract: Objective: Supporting Early Childhood Development (ECD) is an Australian national priority. Aboriginal children in Western Australia's Kimberley region have much higher rates of developmental concerns at school entry than non‐Aboriginal children. We aimed to describe ECD practices in the participating service; document follow‐up of identified developmental concerns; and identify barriers and enablers to incorporating ECD practices into clinic activity. Design: Mixed‐method design incorporating clinical audit and staff interviews. Setting: An Aboriginal Community Controlled Health Service (ACCHS) in the Kimberley region. Participants: A total of 176 children receiving primary health care through the participating ACCHS; interviews with five ACCHS staff members. Main outcome measures: Frequency of developmental enquiry by age and domain; follow‐up of identified developmental concerns; and barriers and enablers to ECD practices. Results: Developmental enquiry was documented for 114 of 176 eligible children (65%), including in 80% of ACCHS child health assessments. Standardised ECD assessments were less common. Staff were aware of the importance of developmental enquiry, however, barriers to increasing ECD practices included a lack of resources and structured staff education, time pressures and a lack of role clarity between the ACCHS and government community health clinic. Conclusions: This study provides insight into ECD practices in an ACCHS setting, highlighting the potential of primary health care to have an enhanced role in ECD if appropriate systems, training and tools are provided. A lack of role clarity across services, combined with poor communication between services, creates a potential risk for missed opportunities to support ECD.